MENINGKATKAN KOMPETENSI APARATUR PEMERINTAH DAERAH DALAM MEWUJUDKAN GOOD GOVERNANCE - Enceng Enceng (Badan Kepegawaian Negara | The National Civil Service Agency, 2008)
As one of indicator for measuring the success of district autonomy is the better the government in serving citizen and lead them to a better life. In fact, district government’s work has not met the expectation that they still can not serve people optimally. Expanding competencies of apparatus to increase their work quality is the critical factor for the success of the district government’s activity. The work of district government’s apparatus toward high quality performance leads to the educational, competencies, and abilities development due to the growth face in times. The expected competencies that the district government’s apparatus being capable of are the ability to analyze problems occur within the citizen and be able to solve them in term of district governmental practical system. Keywords: Competency, Regional Governance, Good Governance.